DNA Fingerprinting and Genetic Diversity in Aus Rice (Oryza sativa L.) Landraces of Bangladesh (Bangladesh Rice Journal, 2018)
The allelic diversity and relationships among 48 Aus rice landraces were determined through DNA fingerprinting using microsatellite (SSR) markers. A total of 14 SSR markers for different chromosomes were used to characterize and differentiate the studied rice genotypes. The number of alleles per locus varied from three alleles (RM118) to 18 alleles (RM44) with an average of 9.88. The polymorphic information content (PIC) varied widely among the loci and ranged from 0.3725 (RM107) to 0.9146 (RM519) with an average of 0.7248. The genetic distance-based results found in the UPGMA clustering system revealed six genetic groups with a similarity coefficient of 0.35. Chakila and Shitki saitta had closest distance in the SSR based genetic distance might have same genetic background. Based on genetic coefficient, the diverse landraces Kasalot, Balam, Pankhiraj, Dular, Hashikalmi, Galong, Panbira, Marichbati, Pidi and Surjomoni could be selected as potential parents for varietal improvement programme. The findings of this study should be useful for varietal identification and could be useful for plant breeders in selecting suitable genetically diverse parents for the crossing programmeBangladesh Rice j. 2017, 21(1): 59-65